Optimasi Konsentrasi PVA (Polyvynil Alcohol) terhadap Karakteristik Dan Aktivitas Antibakteri (Cutibacterium Acnes) pada Masker Gel Peel Off Ekstrak Daun Kelor (Moringa Oleifera L.) - Astrit Sulastri; Hasriyani Hasriyani; Fahrudin Arif (KOLONI, 2026)
Acne is a common dermatological problem in tropical countries with high humidity and pollution levels. One of its causes is the growth of Cutibacterium acnes, which can trigger skin irritation and inflammation. Moringa leaves (Moringa oleifera L.) contain bioactive compounds, including flavonoids, tannins, and saponins, that possess antibacterial properties. This study aimed to determine the optimum concentration of polyvinyl alcohol (PVA) as a film forming agent in a peel off gel mask containing Moringa leaf extract and to evaluate its antibacterial activity against Cutibacterium acnes as well as its physical characteristics. Moringa leaf extract was obtained through maceration using 96% ethanol. Peel off gel mask formulations were prepared with varying PVA concentrations: 10% (F1), 12% (F2), and 14% (F3). Physical evaluations included organoleptic properties, homogeneity, pH, viscosity, spreadability, adhesion, and drying time. Antibacterial activity was assessed using the well diffusion method. Data were analyzed using One Way ANOVA followed by the LSD Post Hoc test. The results showed that all formulations met the required physical characteristics of peel off gel masks. Antibacterial testing demonstrated that F1 produced the largest inhibition zone (8.1 mm),  F2 (7.5 mm) and F3 (6.7 mm). Statistical analysis indicated significant differences among the formulations (p<0.05). The study concluded that variations in PVA concentration influenced the antibacterial activity of the peel off gel mask. Formula F1 containing 10% PVA was identified as the optimum formulation due to its favorable physical characteristics and highest antibacterial activity against Cutibacterium acnes.